Investing in care: A strategy for effective and equitable job creation - Rania Antonopoulos; Kijong Kim; Tom Masterson; Ajit Zacharias (Levy Economics Institute of Bard College, 2010)
Massive job losses in the United States, over eight million since the onset of the 'Great Recession,' call for job creation measures through fiscal expansion. In this paper we analyze the job creation potential of social service-delivery sectors-early childhood development and home-based health care-as compared to other proposed alternatives in infrastructure construction and energy. Our microsimulation results suggest that investing in the care sector creates more jobs in total, at double the rate of infrastructure investment. The second finding is that these jobs are more effective in reaching disadvantaged workers-those from poor households and with lower levels of educational attainment. Job creation in these sectors can easily be rolled out. States already have mechanisms and implementation capacity in place. All that is required is policy recalibration to allow funds to be channeled into sectors that deliver jobs both more efficiently and more equitably.
Keywords: D30; E62; J48; 330; social care; job creation; fiscal expansion; distribution; infrastructure